2016
DOI: 10.1097/md.0000000000004468
|View full text |Cite
|
Sign up to set email alerts
|

Eight years of follow-up after laminectomy of calcium pyrophosphate crystal deposition in the cervical yellow ligament of patient with Coffin–Lowry syndrome

Abstract: Background:We report 8 years of follow-up after decompression to treat cervical myelopathy in a patient with Coffin–Lowry syndrome (CLS). CLS is a rare X-linked semidominant syndrome associated with growth and psychomotor retardation, general hypotonia, and skeletal abnormalities. In this patient, the spinal cord was compressed by calcium pyrophosphate crystal deposition in the cervical yellow ligament (YL). To date, only 1 report has described clinical features after surgery for calcified cervical YL in CLS.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…It may cause neural axis abnormalities and in the most severely affected cases paralysis. Morino et al 7 reported an improvement in neurological function after early laminoplasty at just two weeks and long-term continued ambulation. Therefore, it appears that the detection and early treatment of these abnormalities is imperative.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It may cause neural axis abnormalities and in the most severely affected cases paralysis. Morino et al 7 reported an improvement in neurological function after early laminoplasty at just two weeks and long-term continued ambulation. Therefore, it appears that the detection and early treatment of these abnormalities is imperative.…”
Section: Discussionmentioning
confidence: 98%
“…Winter et al 15 found that thoracic lordosis in patients with AIS significantly impacted their pulmonary function. Multiple recent studies 7 , 10 , 13 have shed light on the effect of these deformities on pulmonary and cardiac function. Bronchial torsion occurs as a result of thoracic kyphoscoliosis, 10 airway compression will occur with thoracic scoliosis, 7 and lordoscoliosis has been associated with both intrathoracic airway compression 13 and extrinsic bronchial obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the age of 14 years, the patient gradually developed quadriplegia because of cervical cord compression induced by the forward shift of the atlas and calcification of the yellow ligament, and he experienced difficulty in walking. The patient underwent laminectomy of the 1st–7th cervical vertebrae under general anesthesia at the age of 15 years [ 10 ] ; however, laminectomy did not resolve his symptoms consistently, that is, his symptoms relapsed and remitted.…”
Section: Case Reportmentioning
confidence: 99%